1989
DOI: 10.1111/j.1460-2695.1989.tb00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Mode (I + Iii) Fatigue Thresholds in a Forging Steel

Abstract: The results of mixed mode (I + 111) fatigue tests on a low pressure steam turbine rotor steel are presented. Tests were performed on a uniaxial servohydraulic fatigue machine fitted with a torsion-bending loading frame. The onset of failure was marked by fatigue facets which grew perpendicular to the maximum principal stress direction. A criterion for mixed mode (I + 111) fatigue thresholds based on the orientation and the crack opening displacement of fatigue cracks is proposed. NOMENCLATURE u = crack length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 12 publications
4
56
0
Order By: Relevance
“…Observations in the literature, such as those of Yates and Miller (1989) also support a correlation between the twist angle and the ratio of stress intensity factors based on the idea of a locally opening mode crack. Cooke and Pollard (1996) also use the maximum energy release rate criterion, the requirement that mode III on incipient crack equal to zero (K III = 0), and the condition that mode I on the incipient crack K I is a maximum and show that all four criteria predict the same twist angle as a function of K ∞ III /K ∞ I as long as K ∞ III /K ∞ I < 1.4; beyond this level the maximum energy release rate criterion exhibits two solution branches.…”
Section: Review Of Prior Work On Mixed Mode I + Iii Fracturementioning
confidence: 67%
“…Observations in the literature, such as those of Yates and Miller (1989) also support a correlation between the twist angle and the ratio of stress intensity factors based on the idea of a locally opening mode crack. Cooke and Pollard (1996) also use the maximum energy release rate criterion, the requirement that mode III on incipient crack equal to zero (K III = 0), and the condition that mode I on the incipient crack K I is a maximum and show that all four criteria predict the same twist angle as a function of K ∞ III /K ∞ I as long as K ∞ III /K ∞ I < 1.4; beyond this level the maximum energy release rate criterion exhibits two solution branches.…”
Section: Review Of Prior Work On Mixed Mode I + Iii Fracturementioning
confidence: 67%
“…The fact that similar phenomena are observed in such diverse materials as glass (Sommer, 1969), alumina (Suresh and Tschegg, 1987), steels (Hourlier and Pineau, 1979;Yates and Miller, 1989;Lazarus, 1997), rocks (Pollard et al, 1982;Pollard and Aydin, 1988;Cooke and Pollard, 1996), PMMA (Lazarus et al, 2008), gypsum and cheese (Goldstein and Osipenko, 2012) strongly suggests that the microstructure of these materials plays little or no role and that the standard tools of macroscopic Linear Elastic Fracture Mechanics (LEFM) should be able to explain the observations made.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these papers were of experimental nature; see the works of (Sommer, 1969;Knauss, 1970;Palaniswamy and Knauss, 1975;Hourlier and Pineau, 1979;Pollard et al, 1982;Suresh and Tschegg, 1987;Pollard and Aydin, 1988;Yates and Miller, 1989;Hull, 1993;Yates and Mohammed, 1994;Hubbard, 1995;Hull, 1995;Cooke and Pollard, 1996;Lazarus, 1997;Lazarus et al, 2001aLazarus et al, ,b, 2008Lin et al, 2010;Goldstein and Osipenko, 2012), among others. All these experimental investigations have shown that the crack propagates through formation of small fracture "facets" (or "lances" in Sommer (1969)'s terminology) which may either abruptly "tilt" or gradually "twist" about the direction of propagation; the wording "crack front segmentation" is often used to designate the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…From the review of literature it appears that equations proposed by Sih [3] and Richard [1] give the best results in description of experiment results. Mixed modes I and III were considered by Yates and Miller [4]. In [4] they proposed a model for description of fatigue crack propagation for mixed modes (I+III), reduced to mode I.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed modes I and III were considered by Yates and Miller [4]. In [4] they proposed a model for description of fatigue crack propagation for mixed modes (I+III), reduced to mode I. Specimens bended in three points were tested.…”
Section: Introductionmentioning
confidence: 99%